2015
DOI: 10.1002/2014gl062575
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in soil pH across major forest ecosystems in China

Abstract: Atmospheric acidic deposition has been a major environmental problem since the industrial revolution. However, our understanding of the effect of acidic deposition on soil pH is inconclusive. Here we examined temporal variations in topsoil pH and their relationships with atmospheric sulfur and nitrogen deposition across China's forests from the 1980s to the 2000s. To accomplish this goal, we conducted artificial neural network simulations using historical soil inventory data from the 1980s and a data set synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 44 publications
(73 reference statements)
3
30
1
Order By: Relevance
“…3a) are most likely due to enhanced NH 3 emissions from natural and fertilized soils, and biological sources such as humans, sewage systems, and organic waste in garbage containers (Chang et al, 2016;Meng et al, 2018). Zhang et al (2018) showed that NH 3 emissions in China show a strong summer peak, with emissions about 50 % higher in summer than spring and autumn. The lowest concentrations of NH 3 , in winter (Fig.…”
Section: Seasonal Variations Of N R Concentration and Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…3a) are most likely due to enhanced NH 3 emissions from natural and fertilized soils, and biological sources such as humans, sewage systems, and organic waste in garbage containers (Chang et al, 2016;Meng et al, 2018). Zhang et al (2018) showed that NH 3 emissions in China show a strong summer peak, with emissions about 50 % higher in summer than spring and autumn. The lowest concentrations of NH 3 , in winter (Fig.…”
Section: Seasonal Variations Of N R Concentration and Depositionmentioning
confidence: 99%
“…Future work based on improved NH 3 emission inventories (e.g. Zhang et al, 2018) and including bidirectional ammonia exchange with the surface is essential to better examine source attribution of N deposition in China.…”
Section: Uncertainties and Limitationsmentioning
confidence: 99%
“…Soil pH will reduce results from an increase in nitrogen deposition [28], which has been occurring on the Tibetan Plateau [50]. Therefore, soil pH has a trend of decreasing, which may promote an increase in soil N.…”
Section: Relationship Between Soil N Density and Soil Phmentioning
confidence: 99%
“…For instance, a major concern has emerged regarding soil acidification in intensive agricultural cropland systems in China, mainly due to the overuse of fertilizer application for pursuing high agricultural production to meet increasing demands for food (Guo et al 2010;Yang et al 2012). Soil acidification induced by N deposition also occurred in coniferous and mixed coniferous and broadleaved forests (Yang et al 2015). In some intensive agricultural ecosystems, such as in wheat-maize cropping systems in a major grain production zone, excessive nitrogen application could decrease grain yield and could easily lead to nitrogen loss, which could result in environmental contamination (Wang et al 2011;Xu et al 2013;Lu et al 2014).…”
Section: Effects Of N Deposition and Consequences Of Excessive N Addimentioning
confidence: 99%